Analysis of Student Midterm Test Scores and The Decline of Learning Interest in Physics - Almi Nursa'bani; Rizal Adimayuda; Arip Nurahman (STKIP Harapan Bima, 2025)
This descriptive study analyzes the Midterm Test (UTS) scores of Physics for grades XII Science 1 and XII Science 2 at SMA Muhammadiyah Banyuresmi and explores the factors behind students' declining interest in learning science. Data were collected through documentation of UTS scores from both classes (37 students each) and analyzed quantitatively to determine passing percentages, and qualitatively to explore possible causes. The results show that the average score in XII Science 1 was 22.97 and in XII Science 2 was 21.76, both far below the minimum mastery criterion (KKM) of 75. Only 8% of students in XII Science 1 and 3% in XII Science 2 passed the KKM. Literature analysis suggests that low scores relate to monotonous lecture-based teaching methods, lack of practicum activities, low mathematical foundations, misconceptions, and low learning motivation. The study concludes that innovative and interactive teaching strategies, such as Problem Based Learning, Quantum Teaching, and Project Based Learning, along with the use of teaching aids and direct observation of physics phenomena, are needed to increase students' interest and achievement in Physics.